2010
DOI: 10.1186/bcr2777
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid synthase phosphorylation: a novel therapeutic target in HER2-overexpressing breast cancer cells

Abstract: IntroductionThe human epidermal growth factor receptor 2 (HER2) is a validated therapeutic target in breast cancer. Heterodimerization of HER2 with other HER family members results in enhanced tyrosine phosphorylation and activation of signal transduction pathways. HER2 overexpression increases the translation of fatty acid synthase (FASN), and FASN overexpression markedly increases HER2 signaling, which results in enhanced cell growth. However, the molecular mechanism and regulation of HER2 and FASN interacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
97
0
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(103 citation statements)
references
References 43 publications
(66 reference statements)
2
97
0
4
Order By: Relevance
“…The relationship between de novo fatty acid synthesis and members of the EGFR family is especially close and bi-directional. 17,18 Our finding, pmEGFR signaling promotes mitochondrial fusion by interacting with/activating FASN to elevate the levels of de novo synthesized palmitate that in turn activates mtEGFR to promote mitochondrial fusion, further supports that FASN or de novo fatty acid synthesis is a part of EGFR's oncogenic machinery.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…The relationship between de novo fatty acid synthesis and members of the EGFR family is especially close and bi-directional. 17,18 Our finding, pmEGFR signaling promotes mitochondrial fusion by interacting with/activating FASN to elevate the levels of de novo synthesized palmitate that in turn activates mtEGFR to promote mitochondrial fusion, further supports that FASN or de novo fatty acid synthesis is a part of EGFR's oncogenic machinery.…”
Section: Discussionsupporting
confidence: 54%
“…HER2 can activate FASN through physical interaction and phosphorylation. 18 EGFR was primarily found in the plasma membrane, where it is activated by its extracellular ligands such as EGF. Besides the plasma membrane, EGFR can also exist in the nucleus 19,20 and in the mitochondrion.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the amplification/overexpression of the genetic driver HER2 defines fatty acid metabolism in one subtype of breast cancers: It has recently been suggested that HER2 directly phosphorylates and thereby activates fatty acid synthase [68]. Thus, fatty acid synthase inhibitors might be potent drugs in HER2 amplified breast tumors [68].…”
Section: Genetic Alterations In Breast Cancer and Their Connection Tomentioning
confidence: 99%
“…There is evidence that HER2 posphorylates FASN, which results in increased enzymatic activity. Blocking FASN phosphorylation and enzymatic activity by either lapatinib (HER2 specific tyrosine kinase inhibitor) or C75 (FASN inhibitor) suppressed invasion of SKBR3 and BT474 cells (Jin et al 2010). In order to sustain this lipogenic phenotype, the cells are in constant demand of cofactors that are essential for glycolysis and fatty acid synthesis.…”
Section: The Altered Metabolism Of Her2/neu-positive Breast Cancermentioning
confidence: 99%